Assessment domestic violence among women in mosul city. - Radhwan Hussein Ibrahim; Aayed A. Bny Uoda (College of Nursing,University of Mosul, 2018)
Violence against anyone is unacceptable. Violence experienced by women, however, particularly intimate partner violence and sexual assault, represents a unique aspect of the wider social problem of violence, and requires specific attention and solutions. Individual experiences of violence against women must be assessed against the backdrop of historical, social, political, cultural and economic inequality of women. This study aims to Assess domestic violence among women in Mosul City. This descriptive study was conducted in two primary health care centers and Court of Appeal in Mosul during 3 months period from 23 December, 2012 to 7 March , 2013. The study sample consists of (500) women in the location of the study who suffered from domestic violence and agree to participation to answer about questionnaire in a direct interview with researcher. The questionnaire subsumed Part (1) concerns physical domestic violence, and includes (13) items focused on violence related with emotional abuse, Part (2) concerns social domestic violence questionnaire, and consists of (13) items, Part(3) concerns emotional domestic violence, and consists of (18) items. Statistical processing was conducted by the use of frequency(F)and percentage(%). A total of 500 women were enrolled in this study; 33% of women were exposed to physical violence, 37% of women were exposed to social violence, 79% of women were exposed to emotional violence. These percentages take into account that every single one of these respondents has been subjected to at least two of these three types .This study shows the causes that lead to uses domestic violence against women and the impact of violence on the women , family ,children and community. The researcher has recommended a serious cooperation with civil society organizations and international bodies concerned with this issue to determine the extent of this problem because posed by economic burdens and that hinder the development of society, and affect the gross national product of the country.